Effects of substrate orientations on the local acceleration in thin film growth: the case of Co on an Al surface - Kim, SP; Chung, YC; Lee, SC; Lee, KR (KOREAN PHYSICAL SOC, 2004)
Many attempts have been made to understand the dynamics of thin film growth by using molecular dynamics. In accordance with the latest results for Co on deposited an Al substrate, which were obtained by using molecular dynamics, the surface compounds turned out to be formed in a few layers. The causes of the surface compound formation were also reported to be a relatively high value of the local acceleration induced by the strong chemical affinity between Co and Al and a low value for the activation barrier. However, since the former investigations reported the local acceleration under ideal conditions, comprehensive approaches are needed for the sake of understanding the actual deposition and growth behaviors of atoms. In the present work, we performed a quantitative analysis of the local acceleration for various deposition energies of the incident atom and its dependence on the surface orientation. Incident 0.1 eV Co atoms were accelerated to about 1.5 similar to 3.5 eV in the vicinity of the Al(001) surface, and this observation was always the same in magnitude, irrespective of the incident energy. Also, the local accelerations were distributed widely for the various surface orientations. Specially, the (111) surface had a higher acceleration on average than any other surfaces [(001), (011)], and the (011) surface had the widest distribution.
Keywords: MOLECULAR-DYNAMICS; DEPOSITION